2001
DOI: 10.1055/s-2001-15419
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Inhibits Steroid Biosynthesis by Human Granulosa-Lutein Cells

Abstract: Absence of leptin secretion compromises reproductive function and fertility in the ob/ob mouse which, when given leptin, shows a rise in serum LH levels and becomes fertile. Recently, the long and active isoform of the leptin receptor was detected in the ovary, indicating that leptin may also show direct gonad-related activity. To examine this, we studied the effect of graded doses of human leptin on estradiol (E2) and progesterone (P4) concentrations in the culture media of human granulosa-lutein cells obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 30 publications
2
35
0
2
Order By: Relevance
“…In this work, we found that leptin is able to induce a biphasic effect on progesterone production. A direct inhibitory action of leptin on steroid hormone secretion has been demonstrated independently by different authors in the ovary (Spicer & Francisco 1997, Zachow & Magoffin 1997, Agarwal et al 1999, Barkan et al 1999, Zachow et al 1999, Ghizzoni et al 2001, Kikuchi et al 2001 and in other tissues (Tena-Sampere et al 2001, Cameo et al 2003. However, findings of both stimulation and inhibition effect with different levels of leptin in ovarian cells in vitro are in agreement with observations by Ruiz-Cortés et al (2003) who found that the effects of leptin are biphasic with regard to stimulation and inhibition of progesterone synthesis.…”
Section: Ctrlsupporting
confidence: 80%
“…In this work, we found that leptin is able to induce a biphasic effect on progesterone production. A direct inhibitory action of leptin on steroid hormone secretion has been demonstrated independently by different authors in the ovary (Spicer & Francisco 1997, Zachow & Magoffin 1997, Agarwal et al 1999, Barkan et al 1999, Zachow et al 1999, Ghizzoni et al 2001, Kikuchi et al 2001 and in other tissues (Tena-Sampere et al 2001, Cameo et al 2003. However, findings of both stimulation and inhibition effect with different levels of leptin in ovarian cells in vitro are in agreement with observations by Ruiz-Cortés et al (2003) who found that the effects of leptin are biphasic with regard to stimulation and inhibition of progesterone synthesis.…”
Section: Ctrlsupporting
confidence: 80%
“…A direct involvement of leptin in ovarian function has been postulated following the demonstration of leptin-receptors in the ovaries of numerous mammalian species (Karlsson et al 1997, Ruiz-Cortés et al 2000, Kikuchi et al 2001. The majorities of studies have suggested that the direct effects of leptin on ovarian cells are inhibitory and can be attributed to attenuation of steroidogenesis (Zachow & Magoffin 1997, Zachow et al 1999, Duggal et al 2000, Spicer et al 2000, Ghizzoni et al 2001, Guo et al 2001. Little is known about the genes targeted by leptin in the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin inhibits IGF-I-stimulated oestradiol secretion from cultured granulosa cells (Spicer & Francisco 1997, Zachow & Magoffin 1997, Zachow et al 1999) and human granulosa lutein cells (Agarwal et al 1999, Greisen et al 2000, Ghizzoni et al 2001, Tsai et al 2002. These findings suggest that leptin has a negative interaction with the intrafollicular IGF system.…”
Section: Introductionmentioning
confidence: 99%